1989
DOI: 10.1159/000234790
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Drugs of Eosinophil Recruitment Induced by Immune Challenge in the Rat

Abstract: The factors responsible for eosinophil recruitment are poorly defined, although both platelet-activating factor (PAF) and cytokines appear to be involved in regulating this process. We compared eosinophil mobilization induced by PAF or antigen injection in the peritoneal cavity of hypereosinophilic rats and the effects of the PAF antagonist BN 52021, the somatostatin analog BIM 23014, and ciclosporin A on this process. PAF induced a significant increase of both peritoneal and circulating eosinophil count. Cicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…The ability of cytokines such as GM-CSF, IL-3, and tumour necrosis factoralpha (TNF-a) [24] to cause a lung eosinophilia has already been demonstrated in guinea-pigs. Other studies have shown a reduction in eosinophil infiltration of the peritoneal cavity of antigen-challenged rats [25,26] and the prevention of the late onset bronchoconstriction in antigen-challenged guinea-pigs [27], when these animals were pretreated with CsA. The present studies extend these findings and show FK506 to be a more potent compound than CsA, which agrees with in vitro results [28].…”
Section: Discussionsupporting
confidence: 91%
“…The ability of cytokines such as GM-CSF, IL-3, and tumour necrosis factoralpha (TNF-a) [24] to cause a lung eosinophilia has already been demonstrated in guinea-pigs. Other studies have shown a reduction in eosinophil infiltration of the peritoneal cavity of antigen-challenged rats [25,26] and the prevention of the late onset bronchoconstriction in antigen-challenged guinea-pigs [27], when these animals were pretreated with CsA. The present studies extend these findings and show FK506 to be a more potent compound than CsA, which agrees with in vitro results [28].…”
Section: Discussionsupporting
confidence: 91%
“…The hypereosinophilia in rat which can be induced by administration of cyclophosphamide or sephadex 48 h before immunization with complete Freund's adjuvant, is significantly decreased by the SS analogue BTM 23014 [63,64]. SS has been shown to enhance the formation of human leukocyte migration inhibiting factor [65].…”
Section: The Influence Of Somutostatin On Hasophils and Eosinophilsmentioning
confidence: 99%